EFEKTIVITAS OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN PROVINSI RIAU DALAM MENYELESAIKAN LAPORAN MASYARAKAT DIBIDANG PELAYANAN PUBLIK BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2009 TENTANG OMBUDSMAN REPUBLIK INDONESIA DI PROVINSI RIAU TAHUN 2013-2014 - Sari, Ria Novia; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Supervision of public service performed by internal and external supervisory. according to article 35 item 2 of Act No. 25 of 2009 on Public Service can be done through oversight by the Ombudsman of the Republic of Indonesia in accordance with the legislation. The Ombudsman of the Republic of Indonesias Riau Province Representative tasked to oversee the implementation of public service in the province of Riau. In this case the effectiveness of the Ombudsman of theRepublic of Indonesia Riau Provincial Legislative need to be assessed in order to realize the objectives of supervision. But in terms of performing the duties and functions of its Ombudsman of the Republic of Indonesia Representative Riau province there are still some obstacles include the lack of human resources, lack of funds, supporting facilities still need to be added in order to support the execution of their duties and functions, as well as the existence of the existence of the Ombudsman of the Republic of Indonesia Representatives of the province of Riau still less among the people. this is what causes his old settlement process and also menghambatan public reports of its operation in the field of prevention.From the research, it can be concluded there are still some tasks Ombudsman of the Republic of Indonesia Representative Riau province that still has not run equally effective, this is due to his existing barriers include the lack of human resources, limited funds, a lack of facilities to support the performance of the Ombudsman of the Republic of Indonesia Representative Riau province, there is still a lack of existence of the existence of the Ombudsman of the Republic of Indonesia Representative Riau Province. To the suggestion of the authors namely the need for additional human resources, an increase in funding, additional support facilities, and the need for socialization evenly in every city / regency in Riau province related to the existence of the Ombudsman of the Republic of Indonesia Representative Riau Province.Keywords : Effectiveness - Representatives of Ombudsman of the Republic ofIndonesia Riau Province - Completion of the public report .